TI_GERICHTE 11.2011.185 vom 30. Dezember 2013 , Protezione dell'unione coniugale: reddito di un lavoratore indipendente - TI Tribunale d'appello (2013)
Protezione dell'unione coniugale: reddito di un lavoratore indipendente